Correlation between immune-related adverse events and therapeutic effects of nivolumab in patients with malignant pleural mesothelioma - Hiroto Yoneda (BMC, 2021)
Abstract Background Nivolumab is used for the treatment of malignant pleural mesothelioma (MPM). However, immune-related adverse events (irAEs) occur in patients treated with nivolumab. Several studies have reported the correlation between irAEs and therapeutic effects of immune checkpoint inhibitor, but none have reported the correlation in MPM. Here we report a retrospective study which shows the correlation between irAEs and therapeutic effects of nivolumab in patients with MPM. Methods This study included patients treated with nivolumab at Tokushima University Hospital from February 2009 to September 2021. We retrospectively reviewed the medical records to evaluate the several clinical factors, such as the presence or absence of irAEs, their severities, progression-free survival (PFS), overall survival (OS) or objective response to the treatment. Results Eleven patients received treatment with nivolumab. Objective response rate was 18.2% and the disease control rate was 90.9%. Median PFS was 6.8 months (95% confidence interval, 1.3 to 11.9 months) and median OS was 15.2 months (95% confidence interval, 8.9 to 21.5 months). IrAEs occurred in eight patients (72.7%), and grade ≥ 2 irAEs occurred in six patients (54.5%). PFS and OS were significantly longer in the grade ≥ 2 irAEs group than in grade < 2 irAEs group (median PFS 13.6 vs. 3.8 months, p = 0.0093; median OS not reached vs. 8.6 months, p = 0.0108). Conclusions This is the first study to report the correlation between irAEs and therapeutic effects in patients with MPM. Because the presence of irAEs may be associated with a favorable clinical outcome, early detection and appropriate management of irAEs will increase the therapeutic benefits to patients.